Temperature and Torque Measurements of Switched Reluctance Actuator with Composite or Laminated Magnetic Cores - Marek Przybylski (Sensors, 2020)
Soft magnetic composite (SMC) materials made of iron powder are more frequently used in construction of electric actuators and motors because of their advantages with respect to Fe–Si electric steel sheets and because they have almost no powder loss. The study deals with measurements of temperature and torque of a low-power rotary switched reluctance actuator, with reference to a commercial actuator and a prototype actuator characterized by stator and rotor cores made of soft magnetic composite materials. Further power loss analysis was also conducted. To assess the actuators, magnetization characteristics and iron loss vs. magnetic flux density at a given frequency were measured according to IEC standards. Results show that the actuator made of soft magnetic composites exhibits higher efficiency and a lower temperature rise of stator and windings in comparison with the commercial actuator.